Nonclinical Safety Assessment of an Inhaled Formulation of Serelaxin: A Recombinant Human Protein in Rats and Cynomolgus Monkeys (Macaca fascicularis). (February 2021) - Flandre, Thierry D.; Hey, Adam S.; Spence, Fiona J.
Serelaxin is a recombinant human relaxin-2 intended for cardiovascular indications. Inhalation was chosen as alternative route to intravenous to allow daily administration for chronic applications and home treatment. A total of 4 short-term studies were conducted in rats and cynomolgus monkeys with inhaled formulation of serelaxin at dose up to 10 mg/kg/d. All rats and cynomolgus macaques receiving serelaxin were exposed to the test item. One rat and approximately 50% of macaques developed immunogenicity, which did not appear to affect exposure. No adverse effect on respiratory function or systemic changes was noted. Both species developed similar microscopic lesions characterized by eosinophilic cell infiltration around bronchi; however, in the rat, this was more pronounced and extended to a perivascular location. In addition, in the rat, serelaxin showed eosinophilic crystalline material associated with macrophages in the alveoli and bronchioles. In macaques, serelaxin induced minimal macrophage infiltrates in alveoli and perivascular/peribronchiolar mononuclear cell infiltrations. The minimal airway eosinophilic/mononuclear inflammatory cell infiltrations were considered to be nonadverse in macaques due to the minimal severity and the lack of any other alterations in the lung parenchyma. In the rat, the presence of eosinophilic crystalline material and macrophage response, characterized as precipitated test article, was considered adverse.